2001
DOI: 10.1116/1.1378009
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective photoelectrochemical etching of nitride materials for defect investigation and device fabrication

Abstract: Photoenhanced electrochemical ͑PEC͒ etching in an unstirred KOH solution under He-Cd laser illumination was used for delineating extended defects in GaN films. When a low-excitation intensity was employed, the process yielded threading vertical features at dislocation sites. Application of an external voltage or a higher-illumination intensity led to high-etch rates with smooth surfaces. Some highly resistive samples, for which no etching was obtained under normal etching conditions, could be etched with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The photoinduced etching technique has been used extensively for defect delineation, 1,2 as well as creating GaN metal-semiconductor field effect transistor gate recesses, 3,4 microelectromechanical structures, 5,6 and electronic device structures. 11,12 In this letter, we focus on band-gap-selective PEC etching of InGaN/ GaN structures. Bandbending near the n-type material surface causes holes to be drawn toward the GaN-electrolyte interface, allowing them to participate in the electrochemical reactions necessary for material removal.…”
mentioning
confidence: 99%
“…The photoinduced etching technique has been used extensively for defect delineation, 1,2 as well as creating GaN metal-semiconductor field effect transistor gate recesses, 3,4 microelectromechanical structures, 5,6 and electronic device structures. 11,12 In this letter, we focus on band-gap-selective PEC etching of InGaN/ GaN structures. Bandbending near the n-type material surface causes holes to be drawn toward the GaN-electrolyte interface, allowing them to participate in the electrochemical reactions necessary for material removal.…”
mentioning
confidence: 99%
“…The high resistance of whiskers to PEC attack was attributed to the negative charge inherent to threading dislocations in n-GaN. 4 Indeed, the photogenerated holes will not contribute to the etching process in case they exhibit fast recombination via defect states at dislocations. An alternative explanation is that dislocations represent regions of decreased potential and the photogenerated holes are repelled from them and confined in the surrounding areas stimulating their dissolution.…”
mentioning
confidence: 99%
“…1 However, regions of enhanced emission have also been observed by cross-sectional CL and attributed to decorated dislocations. 2 Previous investigations [3][4][5] indicate that threading dislocations in n-GaN can be visualized by the formation of whiskers during photoelectrochemical ͑PEC͒ etching. The high resistance of whiskers to PEC attack was attributed to the negative charge inherent to threading dislocations in n-GaN.…”
mentioning
confidence: 99%
“…9,10 Minsky et al 11 demonstrated photoelectrochemical ͑PEC͒ etching to characterize dislocations in GaN. Later, dislocation-selective PEC etching that was consistent with transmission electron microscopy 12,13 ͑TEM͒ and cathodoluminescence 14 was reported and correlation between the dislocation density determined by PEC etching and photoluminescence ͑PL͒ intensity were also found. 15,16 We report the application of PEC etching to the determination of dislocation density in Si-doped, NHE GaN coalesced films grown on 6H-SiC substrates by metalorganic chemical vapor deposition ͑MOCVD͒.…”
mentioning
confidence: 83%